3D printed microfluidic device for online detection of neurochemical changes with high temporal resolution in human brain microdialysate. Issue 11 (16th May 2019) - Samper, Isabelle C.; Gowers, Sally A. N.; Rogers, Michelle L.; Murray, De-Shaine R. K.; Jewell, Sharon L.; Pahl, Clemens; Strong, Anthony J.; Boutelle, Martyn G.
Abstract : Microfluidic devices optimised for real-time monitoring of the human brain. Abstract : This paper presents the design, optimisation and fabrication of a mechanically robust 3D printed microfluidic device for the high time resolution online analysis of biomarkers in a microdialysate stream at microlitre per minute flow rates. The device consists of a microfluidic channel with secure low volume connections that easily integrates electrochemical biosensors for biomarkers such as glutamate, glucose and lactate. The optimisation process of the microfluidic channel fabrication, including for different types of 3D printer, is explained and the resulting improvement in sensor response time is quantified. The time resolution of the device is characterised by recording short lactate concentration pulses. The device is employed to record simultaneous glutamate, glucose and lactate concentration changes simulating the physiological response to spreading depolarisation events in cerebrospinal fluid dialysate. As a proof-of-concept study, the device is then used in the intensive care unit for online monitoring of a brain injury patient, demonstrating its capabilities for clinical monitoring.